Metabarcoding mosquitoes: MinION sequencing of bulk samples gives accurate species profiles for vector surveillance (Culicidae) - Loh, Rebecca Ker; Tan, Tyrone Ren Hao; Yeo, Huiqing; Yeoh, Tze Xuan; Lee, Theodore Tze Ming; Kutty, Sujatha Narayanan; Puniamoorthy, Nalini (Frontiers in Tropical Diseases, 2024)
Mosquitoes (Family: Culicidae) are dominant vectors of pathogens, and their surveillance has been incorporated into major disease control programs worldwide. However, routine, species-level identification of mosquitoes is often a bottleneck for management, and Next Generation Sequencing (NGS) platforms and DNA metabarcoding can revolutionize this process. MinION nanopore technologies promise on-site sequencing and rapid sample processing rates ideal for time-sensitive biosurveillance. Here, we benchmark the results of DNA metabarcoding on the MinION against the Illumina MiSeq platform, which is known for its higher sequencing accuracy. We used metazoan COI mini-barcode primers to carry out DNA metabarcoding of mosquito bulk samples caught during a real vector survey, then compared the mosquito species profiles recovered on each sequencing platform. We also tested the influence of using different trap lures, storage methods, and pooling different specimen body parts on the number of species recovered. We report that mosquito species-level identifications were highly congruent between MinION and Illumina (93% overlap). We also find that CO2 gas cylinders outperformed biogenic CO2 sources significantly, by two-fold. Notably, we demonstrated the feasibility of detecting zoonotic reservoirs and pathogen signals from mosquito bulk samples. We present the first use of DNA metabarcoding on the MinION for vector surveillance and discuss future applications.